Human Resource Management Strategy to Increase Employee Productivity - Fatimah, Sitti Ainun Nur; Idrus, Muhammad Ikram; Maklassa, Maklassa (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to identify and analyze HR management strategies to improve productivity, and determine and analyze the right strategy in HR management to improve its productivity at Yapika General Hospital, Gowa Regency. This study is designed to direct strategic decisions of HR management in an effort to improve its productivity. Strategic decisions in this study include internal and external environmental analysis. Data analysis techniques use IFAS, EFAS, TOWS, and QSPM. The results of the study indicate that the right strategy in human resource management to improve employee productivity at RSU Yapika Gowa Regency is to build strategic partnerships with Puskesmas in the surrounding area to strengthen health services collaboratively with the reason to create synergy in delivering health services collaboratively so that employees can work more efficiently and focused; increasing the capacity of human resources who can get training and skills development from collaboration with Puskesmas to improve HR competency which leads to increased productivity; through collaboration, the quality of health services provided can be improved because human resources who feel that they are part of a larger system tend to be more motivated and committed to their work; this partnership allows access to additional resources, such as medical devices and the latest information on health practices that can help human resources in carrying out their duties better; partnerships with Puskesmas allow RSU Yapika to be more responsive to the health needs of the community because human resources involved in programs that have a direct impact on the community will feel higher job satisfaction.